2012
DOI: 10.1371/journal.pntd.0001840
|View full text |Cite
|
Sign up to set email alerts
|

Hantavirus Pulmonary Syndrome in Santa Cruz, Bolivia: Outbreak Investigation and Antibody Prevalence Study

Abstract: We report the results of an investigation of a small outbreak of hantavirus pulmonary syndrome in 2002 in the Department of Santa Cruz, Bolivia, where the disease had not previously been reported. Two cases were initially reported. The first case was a physician infected with Laguna Negra virus during a weekend visit to his ranch. Four other persons living on the ranch were IgM antibody-positive, two of whom were symptomatic for mild hantavirus pulmonary syndrome. The second case was a migrant sugarcane worker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 31 publications
1
18
0
6
Order By: Relevance
“…[10][11][12][13] Os casos de cura em pessoas do sexo masculino em convalescentes por SPH descritos nesta pesquisa mostram similaridade com outros estudos que aponta para os fatores prognósticos da infecção por hantavírus e influência na resposta imune inata e adaptativa que podem contribuir na patogênese das doenças infecciosas. 6,14 O dimorfismo sexual nas infecções é discutido, pois homens e mulheres diferem na susceptibilidade a infecções e a razão para estas diferenças é multifatorial, sendo induzidas pelos hormônios sexuais e seus efeitos na expressão gênica e no sistema imune, sendo importante destacar as diferenças fisiológicas inatas entre sexos.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…[10][11][12][13] Os casos de cura em pessoas do sexo masculino em convalescentes por SPH descritos nesta pesquisa mostram similaridade com outros estudos que aponta para os fatores prognósticos da infecção por hantavírus e influência na resposta imune inata e adaptativa que podem contribuir na patogênese das doenças infecciosas. 6,14 O dimorfismo sexual nas infecções é discutido, pois homens e mulheres diferem na susceptibilidade a infecções e a razão para estas diferenças é multifatorial, sendo induzidas pelos hormônios sexuais e seus efeitos na expressão gênica e no sistema imune, sendo importante destacar as diferenças fisiológicas inatas entre sexos.…”
Section: Discussionunclassified
“…13 Em um estudo realizado em Santa Cruz, Bolívia, concluiu que os casos de SPH ocorreram em áreas de transição da floresta para pecuária e cultivo de cana-de-açúcar, reforçando então que essa relação próxima às áreas de transformação ambiental aumentam o risco de infecção. 10 Na Argentina, a fragmentação da paisagem nativa causada pela silvicultura e pela agricultura também favoreceu o crescimento excessivo e a distribuição mais ampla dos roedores. 13 Curiosamente, pode-se aplicar tais observações para o estado de Mato Grosso e suas áreas de cultivo, pois a vegetação e o clima equatorial do estado fornecem um excelente microambiente para a manutenção de reservatórios para roedores silvestres.…”
Section: Aspectos Clínico-epidemiológico Dos Pacientes Convalescentesunclassified
“…The lack of reported human cases could mean that the frequency of infected rodents, or of human contact with them, is low; that human infection occurs but is asymptomatic or too mild to be recognized; or that HPS is misdiagnosed by clinicians who are unfamiliar with the condition and lack access to diagnostic testing. In some areas of South America, including Bolivia, Paraguay, Argentina, and Chile, a high prevalence of hantavirus IgG in humans has been reported, but reports of cases of HPS have been infrequent ( 14 ) . …”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, only a limited number of studies on these infections have been performed in certain countries. In Bolivia, South America, fewer than 20 studies about hantaviruses, in any field of knowledge, have been published (Montgomery et al, 2012;Montoya-Ruiz et al, 2014). A study performed in 2002 but published in 2012 is currently the most recent available description of a hantavirus outbreak in the country (Montgomery et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In Bolivia, South America, fewer than 20 studies about hantaviruses, in any field of knowledge, have been published (Montgomery et al, 2012;Montoya-Ruiz et al, 2014). A study performed in 2002 but published in 2012 is currently the most recent available description of a hantavirus outbreak in the country (Montgomery et al, 2012). This study basically reported two serologically confirmed cases in the area of Santa Cruz de La Sierra (or simply, Santa Cruz), a department in the southeast area of the country close to the border with Brazil and Paraguay (Figure 1).…”
Section: Introductionmentioning
confidence: 99%